Research on fatigue crack propagation process of fracturing pumphead. (October 2020) - Zhang, Si; Zhou, Sizhu; Li, Meiqiu
Highlights: Whole fatigue crack propagation process of pumphead is calculated. In high/low stress zone of pumphead, KI increases/decreases with crack length. A wave peak appears in the a - K I curve around the step structure. Abstract: Fracturing pumpheads are a key and crucial component in fracturing technology. Fatigue crack failure greatly decreases the pumphead working life and operational efficiency. This paper describes an analytical model for a five-cylinder fracturing pumphead using the submodel method with the re-meshing technique to analyze its fatigue crack propagation process. Changes in the crack face, a - K I curve (crack length a and stress intensity factor K I ), and a - N curve (number of fatigue loading cycles N ) during crack propagation are considered. The results show that the crack failure of the fracturing pumphead results primarily from mode-I cracks. During crack propagation, the curvature of the crack front gradually decreases due to the higher stress intensity factor K I at the pressured inner surfaces of the pumphead. The stress distribution on the pumphead greatly influences the change law for the a - K I curve. When the crack tip localizes in the high stress zone, K I increases with the crack length a ; when the crack tip localizes in the low stress zone, K I decreases with the crack length a . The step structure of the pumphead also influences changes to the a - K I curve. Around the step structure, a wave peak appears in the a - K I curve, but the influence is localised and its effect on the a - N curve is not significant.